Formation of chitosan nanoparticles to encapsulate krill oil (Euphausia superba) for application as a dietary supplement. (February 2017) - Haider, Junaid; Majeed, Hamid; Williams, P.A.; Safdar, Waseem; Zhong, Fang
Abstract: Encapsulation of krill oil (KO), a rich source of eicosapentanoic (EPA) and docosahexanoic acid (DHA) was carried out in chitosan-TPP (tripolyphosphate) nanoparticles using a newly developed two-step process (i.e, formation of emulsion and later electrostatic interaction of chitosan with TPP). The encapsulation of KO in chitosan nanoparticles (CSNPs) was confirmed by using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and Thermogravimetric analysis (TGA) techniques. Loading capacity (LC) and encapsulation efficiency (EE) of the obtained particles were about 9–25 and 33–59% respectively, when the initial KO content was in the ratio of 0.25–1.25 g/g of Chitosan. Bulk KO showed less protection to oxidation and showed more formation of hydroperoxides during first week as noted by FTIR. However, KO loaded CSNPs showed better prevention of KO towards oxidation with less hydroperoxide formation even after two weeks of storage at elevated temperature (45 °C). The obtained KO-loaded CSNPs were irregular in shape with an average particle diameter of <130 nm as observed by SEM. The results obtained confirmed the suitability of the emulsion and later electrostatic interaction of CS with TPP for the formation of KO loaded CSNPs with greater EE & LC, which will enhance their usage in the Food and Pharmaceutical industries. Graphical abstract: Highlights: KO loaded CSNPs were prepared using emulsion-electrostatic interaction method. KO loaded CSNPs were irregular in shape with average diameter of <130 nm. CSNPs successfully entrap KO as evident by FTIR. KO loaded CSNPs prevented formation of hydroperoxides at elevated temperature.